First step is to distrubute:
-3(10x-3)
-3*10x=-30x
-3*-3=9
10(3x-3)
10*3x=30x
10*-30=-30
Therefore you now have -30x+9+30x-30=x-7
Next combine like terms
-30x+30x=0x
9+-30=-21
-21=x-7
add 7 to each side
x=-14
2006-12-10 03:39:55
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
-30x +9 + 30x -30 (I assume there should have been a close-parenthesis after the -3) = x-7. 9 - 30 = x - 7. -21 = x - 7. -14 = x.
2006-12-10 11:36:27
·
answer #2
·
answered by Amy F 5
·
0⤊
0⤋
I'll assume you forgot the last parenthesis, and that I'm solving for x.
-30x+9 +30x-30=x-7
-21=x-7
-14=x
2006-12-10 11:40:53
·
answer #3
·
answered by DM 2
·
0⤊
0⤋
x=13
2006-12-10 11:35:37
·
answer #4
·
answered by Bao L 3
·
0⤊
0⤋
-3(10x-3)+10(3x-3)=x-7
-30x+9+30x-30=x-7
-30+-21+30x=x-7
-30x+30x=x-28
0x=x-28
-x=-28 (multiply both sides by -1)
x=28
2006-12-10 14:53:11
·
answer #5
·
answered by ♥KiYa♥ 3
·
0⤊
0⤋
first multiply everything and put everything on the left side and u will get
-30x+9+30x-30-x+7=0
Then add it up and u will get X= -14
2006-12-10 12:40:31
·
answer #6
·
answered by edik 4
·
0⤊
0⤋
- 30x +9 +30x - 30= x-7 ( you delete -30x and +30X )
9-30 =x-7
-21=x-7
-x=-7+21
-x= 14
x=-14
2006-12-10 11:44:17
·
answer #7
·
answered by invisible1 4
·
0⤊
0⤋
-3(10x-3)+10(3x-3)=x-7
-30x+9+30x-30=x-7
-21=x-7
-21+7=14
14=x
2006-12-10 11:42:57
·
answer #8
·
answered by jessica_the_rat 1
·
0⤊
0⤋
x=-14
2006-12-10 11:43:07
·
answer #9
·
answered by chriso99 2
·
0⤊
0⤋
x=-14
2006-12-10 11:37:38
·
answer #10
·
answered by moha 1
·
0⤊
0⤋